2020
DOI: 10.1038/s41396-020-00847-0
|View full text |Cite|
|
Sign up to set email alerts
|

Quorum sensing provides a molecular mechanism for evolution to tune and maintain investment in cooperation

Abstract: for helpful suggestions and careful review of the manuscript.

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

3
11
0

Year Published

2021
2021
2022
2022

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 23 publications
(31 citation statements)
references
References 81 publications
3
11
0
Order By: Relevance
“…In agreement with previous work [ 16 , 35 ], we find that in the absence of alternate sources of nutrition (λ 0 = 0), QS reduces the probability of cheater fixation for a wide range of starting population compositions ( Fig 2 ). We calculate the probability of cheaters fixing ( Eq 9 ) in a small population with starting compositions satisfying 0 < n , 0 < m , and n + m ≤ 100.…”
Section: Resultssupporting
confidence: 92%
“…In agreement with previous work [ 16 , 35 ], we find that in the absence of alternate sources of nutrition (λ 0 = 0), QS reduces the probability of cheater fixation for a wide range of starting population compositions ( Fig 2 ). We calculate the probability of cheaters fixing ( Eq 9 ) in a small population with starting compositions satisfying 0 < n , 0 < m , and n + m ≤ 100.…”
Section: Resultssupporting
confidence: 92%
“…In agreement with previous work [14, 25], we find that in the absence of alternate sources of nutrition (λ 0 = 0), QS reduces the probability of cheater fixation for a wide range of starting population compositions (Fig. 2).…”
Section: Resultssupporting
confidence: 92%
“…Our results demonstrate that PAEs may similarly stimulate biofilm formation, although an etiological connection to their endocrine disruption potential seems tenuous. Moreover, although upregulation of QS genes has been reported in response to chemical stress, further research is needed to determine whether the observed upregulation (Figure ) was a response to PAE-related stress that is conducive to biofilm formation as a defense mechanism.…”
Section: Resultsmentioning
confidence: 98%